'The village and the world': competing agendas in teacher research – professional autonomy, interpretational work and strategic compliance. Issue 1 (2nd January 2021) - McLaughlin, Colleen; Wood, Elizabeth
ABSTRACT: In this paper, we explore Lawrence Stenhouse's provocation that too much research has been conducted for the world and not enough for the village. This provocation has taken on additional significance in contemporary global policy contexts where neoliberal systems of governance incorporate discourses of educational effectiveness, measurement, standards, quality and sustainable development. Reform movements draw attention to what forms of professional development are effective in the complex global-national policy agendas, with diverse cultural-historical and socio-political contexts. Furthermore, teachers' work is changing and intensifying under neoliberal systems of governance, specifically what they have to do to interpret and not just to implement policies. Drawing on two contrasting case studies of teacher research in England and Kazakhstan, we examine 'outside in' and 'inside out' approaches to teacher development. We problematize the concepts of teacher autonomy, the interpretational work of teachers in the context of policy intensification, and strategic compliance as a pragmatic and necessary response to policy frameworks and their intended and unintended consequences. We conclude by suggesting a hybrid, dialectical approach to professional development which sustains teacher autonomy and professionalism.